First record and redescription of Paguristes tomentosus (Paguroidea: Diogenidae) in the Áncash region, Peru - Nizama-Chapoñan, Angelo (2025)
This article presents the first record and redescription of Paguristes tomentosus for the Áncash region in Peru, based on three specimens collected on March 13, 2024, in El Ferrol Bay. Photographs and a detailed description of their morphological characteristics are provided to aid in accurate identification. These findings contribute to the understanding of marine biodiversity in the region.